Subversi Naratif Paulus di Areopagus (Kisah Para Rasul 17:22–31): Kerangka Apologetika Kontekstual untuk Era Digital - Paraso, Srifika; Juanta, Elkria (Views : Jurnal Teologi dan Biblika, 2025)
The pluralist digital age presents a fundamental challenge to Christian apologetics, demanding a model that goes beyond traditional propositional argumentation. The epistemological environment of the internet, characterized by a thirst for novelty, flat authority, and fragmented personal narratives, often renders classical apologetic approaches ineffective. This study aims to construct a contextually relevant model of apologetics by performing a narrative exegesis of Paul's speech on the Areopagus in Acts 17:22–31. Using a qualitative method based on narrative criticism, this study analyzes the rhetorical and theological strategies used by Paul as described by Luke. The results of the study show that Paul did not simply accommodate or confront Hellenistic philosophy, but applied the strategy of "Narrative Subversion" to enter the mindset of his audience, retelling their narrative from within, and offering it to the truth of the Gospel. The results obtained from this study are that the "Areopagus Model", which is based on the strategy of Narrative subversion, is based on four principles: compassionate engagement, identification of an altar to a God unknown in culture, and dialogical posture. This model offers a powerful framework for contemporary apologetics, capable of meaningfully interacting with digital culture without compromising the core of the Christian message.